The Effects of Chess Instruction on Academic and Non-Cognitive Outcomes: Field Experimental Evidence from a Developing Country - Asadul Islam; Wang-Sheng Lee; Aaron Nicholas (Institute of Labor Economics (IZA), 2019)
We conduct a randomized field experiment to investigate the benefits of an intensive chess training program undertaken by primary school students in a developing country context. We examine the effects on academic outcomes, and a number of non-cognitive outcomes: risk preferences, patience, creativity and attention/focus. Our main finding is that chess training reduces the level of risk aversion almost a year after the intervention ended. We also find that chess training improves math scores, reduces the incidence of time inconsistency and the incidence of non-monotonic time preferences. However, these (non-risk preference) results are less conclu-sive once we account for multiple hypothesis testing. We do not find any evidence of significant effects of chess training on other academic outcomes, creativity, and attention/focus.
Keywords: C93; D80; I21; 330; chess training; math; non-cognitive outcomes; risk; randomized experiment